Peranan Pengendalian Berbasis Audit Sistem Informasi untuk Pengembangan Strategi Perusahaan Berbasis Komputer (Suatu Bahasan Teoritis atas Faktor Penentu Keberhasilan dan Penyimpangan Penerapan Sistem Informasi dalam Suatu Organisasi Usaha) - Idris Asmuni; Rangga Firdaus (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
An Information systems requires a control to handle the financial activities. The company strategics isthe main factor that makes information must be presented in good reports. The procedures of the systems cangive description about the stakeholders in using the systems components through their philosophy in order tounderstand some possible lacks any time for the survival organization.This paper attempts to explain that there is straight comparison between the audit on information systemsand the strategics developed by decision makers. The management scope has some limitations related to themethods in evaluating its goal that every aspect of the systems control needs to be documented so the systemsdevelopers recognize the quality of management’s achievement. The Decision makers such as manager in everylevel needs the information to take action by considering the mathematics calculation and another variablesOne of these is the accounting information control systems.Theoretically, the main factor to support management policy is the mutual work of personnel systemsin developing the existence of information fully. It is understandable that the process to achieve the successfullof business is done by not forsaking the exposures in business and the analysis method in evaluating theorganization.Keywords: control systems, audit information, management’s achievement, exposures in business and analysismethod